Energy efficient, facile and cost effective methodology for formation of an inclusion complex of resveratrol with hp-β-CD. (11th September 2015) - Kaur, Khushwinder; Uppal, Shivani; Kaur, Ravneet; Agarwal, Jyoti; Mehta, Surinder Kumar
Abstract : A stable inclusion complex was obtained by using a greener, energy proficient approach via an ultrasonic method. Abstract : A distinctive, effortless, proficient and innovative process for preparation of an inclusion complex (IC) of resveratrol (Res) with hp-β-CD was developed. The methodology overcame the hindrance of low solubility of Res which is a potential anticancer agent and makes its use more practical. The strategy involved the utilization of a microwave meant for conventional use and the process of sonication in the laboratory. It considerably saved time and labour besides cutting down on energy consumption. The prepared inclusion complexes were characterised by FTIR, UV-visible absorption spectroscopy, NMR, TGA, DSC, XRD and CHNS analysis. Phase solubility studies along with Gaussian studies proved the formation of a 1 : 1 complex whose physical nature and stability were studied using XRD and UV-visible absorption spectroscopy, respectively. This effortless and economical process could pave the way for the formation of inclusion complexes of other nutraceuticals and pharmaceuticals.